2014
DOI: 10.1177/1759091414554946
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sutherlandia and Elderberry Mitigate Cerebral Ischemia-Induced Neuronal Damage and Attenuate p47phox and Phospho-ERK1/2 Expression in Microglial Cells

Abstract: Sutherlandia (Sutherlandia frutescens) and elderberry (Sambucus spp.) are used to promote health and for treatment of a number of ailments. Although studies with cultured cells have demonstrated antioxidative and anti-inflammatory properties of these botanicals, little is known about their ability to mitigate brain injury. In this study, C57BL/6 J male mice were fed AIN93G diets without or with Sutherlandia or American elderberry for 2 months prior to a 30-min global cerebral ischemia induced by occlusion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The authors have suggested that NOX activation arose in medium spiny neurons and endothelial cells at the early phase and in reactive microglia at the late phase. Additionally, increased p47 phox immunoreactivity was demonstrated in the hippocampus and striatum of the same mice strain 72 hours after 30 minutes of global cerebral ischemia [ 57 ]. Supplementation with vitamin D3 prior to ischemia, in our study, was followed by reduced expression of gp91 phox and p47 phox subunits in both the cortex and hippocampus, increased expression of p22 phox in the cortex and decreased expression of this subunit in the hippocampus, and increased expression of p67 phox in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have suggested that NOX activation arose in medium spiny neurons and endothelial cells at the early phase and in reactive microglia at the late phase. Additionally, increased p47 phox immunoreactivity was demonstrated in the hippocampus and striatum of the same mice strain 72 hours after 30 minutes of global cerebral ischemia [ 57 ]. Supplementation with vitamin D3 prior to ischemia, in our study, was followed by reduced expression of gp91 phox and p47 phox subunits in both the cortex and hippocampus, increased expression of p22 phox in the cortex and decreased expression of this subunit in the hippocampus, and increased expression of p67 phox in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Similar anti-inflammatory activity was reported in murine macrophages, but did not appear to be mediated by sutherlandiosides or sutherlandins, which are glycosylated derivatives (Lei et al, 2015a). Moreover, our recent in vivo studies demonstrated that dietary Sutherlandia mitigates cerebral ischemia-induced neuronal damage, in part by attenuating p47phox and phospho-ERK1/2 expression in microglial cells(Chuang et al, 2014). The present study showed that Sutherlandia extracts not only inhibit LPS-induced NF-κB activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, promising preclinical research exists. Mice fed diets containing American elderberry suffered substantially less disability after 24 h and less neuronal cell death after 3 days in response to global cerebral ischemia (effectively, an induced stroke) than non-supplemented mice (Chuang et al 2014 ). Flowers of Sambucus cerulea , which was once treated as a subspecies of S. nigra though it is morphologically distinct (Applequist 2015 ), are used by members of the North American Lumbee tribe to alleviate symptoms of Parkinson’s disease, and in vitro the extract has neuroprotective activities, including improvement of mitochondrial function in neurons and protection against rotenone neurotoxicity (de Rus Jacquet et al 2017 ).…”
Section: Emerging Health Benefitsmentioning
confidence: 99%